Aplicação de biofertilizante, composto e uréia na produção de capim tanzânia (Panicum maximum, Jacq.) sob irrigação - Junqueira, Juliana Bega [UNESP] (2015)
The objective is to describe the effects of organic fertilization associated with irrigation on production and quality of tanzania grass (Panicum maximum, Jacq cv Tanzania). The review was conducted at the Faculdade de Ciências Agrárias e Veterinárias (FCAV) - Universidade Estadual Paulista (UNESP), in Jaboticabal, São Paulo. Was evaluated the effects of fertilization with urea; fertilization with biofertilizer (from the manure digestion of dairy cattle); fertilization with compost (from the dairy cattle manure) and without fertilization, in two irrigation levels (absence and presence). The experiment was conducted in two phases: the dry season (April to September) and the rainy season (October to March). Was used in the study a randomized blocks. The forage was cut performed after the canopy was intercepting 95% of photosynthetically active radiation. Mass analyzes were performed to quantify the production, morphological composition and chemical analysis in order to evaluate the effect of treatments on production potential and quality of the plant. Nitrogen fertilization promoted increase in leaf area, maximizing production in favorable weather conditions. Irrigation increased the mass production of fodder in the off season, making the system more stable, ensuring satisfactory result for the fertilization and management in the dry season. The urea treatment showed the best results in production of forage mass, though the biofertilizer treatment should be nominated as best organic fertilizer option, because the quality of forage produced, environmental gain and mass production was better